Breathing Easier - With the right ventilation controls and techniques, underground stone operators can create healthier work environments. - Roy H. Grau (The National Institute for Occupational Safety and Health (NIOSH), 2009)
Increased awareness of a healthy work environment is common to all industries and the stone industry is no exception. The presence of operating diesel equipment, welding, stone production blasting, and silica dust in a working environment all contribute to air quality issues in underground stone mines. Particularly recognized is the exposure of workers to diesel particulate matter (DPM). Recent regulations call for a DPM standard of 160TC ug/m3 (TC = Total Carbon). The National Institute for Occupational Safety and Health (NIOSH) has conducted research to improve the ventilation of these mines and consequently reduce the exposure of workers to harmful airborne contaminants. The results have shown that the ventilation of underground stone mines can be significantly enhanced using improved ventilation controls and techniques. Large-opening stone mines present specialized ventilation challenges because their entries are much larger than in other types of mines. Most stone mines have entries about 40 feet wide and up to 30 feet high, with bench areas that may extend even higher. These large entries present the positive opportunity to move large air quantities at relatively low mine fan pressures resulting in lower fan horsepower and reduced operating costs. However, the difficulty in ventilating large-opening mines is that even with large air volumes, the air velocity is often less than 100 feet/minute. Higher ventilation velocities more quickly dilute and remove contaminants from the face areas. Higher ventilation airflow velocities can be achieved by effective ventilation planning and proper choice of ventilation fans.